Surface passivation of MgAl2O4 spinel powder by chemisorbing H3PO4 for easy aqueous processing - Olhero, Susana M (Langmuir : the ACS journal of surfaces and colloids, 2008)
A stoichiometric MgAl 2O 4 spinel (MAS) powder was synthesized by heat treating at 1400 degrees C for 2 h a compacted mixture of alpha-Al 2O 3 and calcined caustic MgO, followed by crushing and milling. The surface of this powder was then passivated against hydrolysis with H 3PO 4 and Al(H 2PO 4) 3 in an ethanol solution. The as-passivated powder could then be dispersed in water using tetramethylammonium hydroxide (TMAH) and an ammonium salt of poly(acrylic acid) (Duramax D-3005) as dispersing agents and gelcast to form green consolidates with relatively high strength (>15 MPa). The good dispersing behavior of the passivated powder in water was confirmed by the low viscosity of its suspension containing 41-45 vol % solids, demonstrating the viability of replacing organic solvents by water in colloidal processing of MAS-based ceramics. The Fourier transform infrared (FT-IR), X-ray diffraction (XRD), and energy dispersive X-ray (EDAX) studies revealed that only negligible amounts of phosphate ions at the surface are required to effectively protect the powder from reacting with water